The prevalence of stress urinary incontinence in women studying nursing and related quality of life - Opara, Józef; Czerwińska-Opara, Wioletta Ewa (Menopause Review/Przegląd Menopauzalny, 2014)
Urinary incontinence is a growing problem that affects millions of people worldwide. The purpose of this study was to assess the prevalence of stress urinary incontinence (SUI) in women studying nursing. Respondents completed a questionnaire assessing urinary incontinence, severity of symptoms and quality of life. Short forms to assess symptoms of distress for urinary incontinence and quality of life: UDI-6 and IIQ-7 have been used. The study’s conclusions are as follows: 1) among the 113 interviewed women, stress urinary incontinence (SUI) was observed in 25% of respondents; this prevalence is similar to the age-matched population; 2) among the triggering factors mentioned in stress urinary incontinence the most frequent were: coughing, laughing and sneezing; 3) moderate impact of incontinence on quality of life has been shown, but this effect was not statistically significant.